Consumer Protection and Organizers' Responsibilities for Concert Cancellations in Indonesia: Case Study ‘Berdendang Bergoyang’ Festival 2022 - Sakti, Muthia; Aurelia, Amanda (International Journal of Business, Law, and Education, 2024)
This research discusses the legal protection of consumers and the responsibility of event organizers for concerts that are canceled, with a case study of the 2022 Berdendang Bergoyang Festival. Canceled concerts often have a negative impact on consumers and challenge the organizers' legal responsibilities. This research aims to analyze the legal aspects involved in concert cancellations, as well as to evaluate the effectiveness of existing consumer protection regulations. The research method used is normative juridical legal research with a case study approach. The research results show that there is a lack of clarity in the legal framework governing concert cancellations, which can lead to conflict between consumers and organisers. In addition, consumer protection does not yet fully cover event cancellation situations that are beyond the organizer's control. Therefore, it is necessary to improve consumer protection regulations and increase legal awareness among event organizers. This research contributes to understanding the legal dynamics related to concert cancellations and formulating recommendations for improving regulations that can increase consumer legal protection and clarify organizers' responsibilities in dealing with canceled concert situations held.